383 Effect of trace mineral source on heifer reproductive performance. (5th December 2019) - Perry, George A; Perkins, Stephanie; Northrop, Emmalee; Rich, Jerica; Epperson, Kaitlin; Mayes, Sarah; Wright, Cody; Russell, Jason
Abstract: Trace minerals are known to play important roles in early embryo development. The study objective was to determine effects of trace mineral source on heifer reproductive performance. Over two years, beef heifers (n = 130) were randomly assigned to two pens and two treatments, within each pen, based on breed, age, and BW. From weaning through the breeding season, all heifers were individually fed a basal diet of grass hay, corn silage, and a supplement pellet (soybean hulls, dried distiller's grains plus solubles, minerals, vitamins and monensin). Cobalt, Cu, Mn, and Zn were supplemented with either complexed sources (Availa-4) or inorganic sources (Cu, Mn, and Zn hydroxychlorides; Intellibond C, M, and Z) and Co as CoSO4 . Blood samples were collected bi-weekly, and a reproductive tract score (RTS) was collected 30 d prior to breeding to determine pubertal status. All animals were synchronized and artificially inseminated (AI). Pregnancy status was determined by lymphocyte gene expression on d 17, 19, and 21; by circulating concentrations of pregnancy associated glycoproteins (PAGs) on d 22, 23, 24, 25, 26, 27, and 28; and by transrectal ultrasonography on d 30 and 60 after AI. Embryonic loss was defined as when a previously pregnant animal was subsequently diagnosed not pregnant. Data were analyzed using the MIXED procedure in SAS. Puberty (P = 0.44), pelvic area (P = 0.74), RTS (P = 0.49), and estrus expression (P = 0.82) were not influenced by treatment. There was no effect of treatment (P = 0.37) or treatment by time (P = 0.19) on pregnancy, but there was a weak tendency (P = 0.13) for decreased embryonic loss among heifers supplemented with complexed trace minerals (27±6%) compared to inorganic minerals (38±6%). In summary, source of trace mineral did not affect puberty, RTS, pelvic area, or overall pregnancy success, but feeding complexed trace minerals tended to increase embryo survival from d 17 to 60.